Desain Akuntansi Rumah Tangga di Bulan Ramadhan - Krisno Septyan; Danang Mintoyuwono (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to design household accounting to achieve the goal of Ramadan, namely taqwa. This study is deductive and normative, derived from absolute truth sources related to the month of Ramadan. Finances in the month of Ramadan have a surplus condition caused by the increasing of home-based business production and the holiday allowances. This surplus condition can be allocated (in part) to facilitate activities in the month of Ramadan, for example giving iftar to others, giving charity, and facilitating Itikaf activities on the last ten nights. Funds can also be allocated to pamper yourself during the day such as taking an online vehicle when commuting to work, not cooking during the day to prepare iftar, all of this is done to save energy that you can worship at night maximally.